The inclusive society? : social exclusion and New Labour - Levitas, Ruth, 1949- (Basingstoke : Palgravae Macmillan, 2005)
An examination of the idea of social exclusion and the new political language of social cohesion, community, stakeholding and inclusion, this book examines the actions and rhetoric of the Labour Party and Labour Government under Tony Blair's leadership.
Previous edition: 1998.
Includes bibliographical references (pages 261-268) and index.
Keywords: Marginality, Social -- Government policy -- United Kingdom; Poverty -- Government policy -- United Kingdom; Labor policy -- United Kingdom; Great Britain -- Social policy -- 1979-; Great Britain -- Social conditions -- 1945-